Using Wall Charts to Enhance Early Reading Skills among First Grade Students - Junita Irawati; Irawati, Junita; Handayani, Pipit Mugi; Sormin, Salman Alparis (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
This research aimed to improve students' reading skills using Wallchart learning media, designed through Classroom Action Research (CAR), based on the Kemmis & Taggart model. This Classroom Action Research aimed to provide innovative actions and solutions to obstacles encountered in the learning process. This research was conducted at SD Negeri 086 Dalam Lidang, Panyabungan District, Mandaling Natal Regency, with a total population of 24 first-grade students. Data collection techniques included observation and reading skill tests. The results showed increased reading skills, as evidenced by the number of students who completed the reading program reaching 63.90% in Cycle 1 and 82.65% in Cycle 2. Wall Chart: Representing complex information with a very realistic, simple, and attractive visual design, it can be used as an independent learning tool that can be seen anytime because it is mounted on a wall or in any particular corner. Therefore, using Wallchart learning media in Indonesian language learning can improve elementary school students' reading skills.